Student Perceptions of Project-Based Learning When Studying ‘Information Systems’ in an ICT Engineering Program: Taking Advantage of Active Learning - Josep Petchamé; Ignasi Iriondo; Odalys Torné; Francesc Solanellas (Education Sciences)
This article presents a case study on the way of teaching and learning the subject ‘Information Systems’ to ICT (Information and Communication Technology) engineering students, which is based on an active learning strategy implemented through a Project-Based Learning (PjBL) method, a practice that facilitates knowledge acquisition in addition to enhancing diverse learning outcomes such as teamwork, critical thinking, and analysis, or communication skills. This study aims to present the students’ perceptions once they have undertaken the whole subject, to better understand the different positive and negative elements associated with PjBL implementation according to their opinions. Students’ perceptions of PjBL were obtained through a survey utilizing the Bipolar Laddering (BLA) technique, which allows them to identify their experiences in terms of both beneficial and challenging aspects, as well as potential improvements to their experiences. On one hand, the most relevant findings on their PjBL experience assessed as positive are presented as follows: to work by themselves on a real project related to the working world; to be able to apply the theoretical topics explained during the class sessions; to have highly talented instructors; to experience a very dynamic and effective way of learning; to give a final presentation to their classmates and the instructors; and to work in groups. On the other hand, when analyzing the core negative perceptions, the following ones were highlighted by the surveyed students: undertaking just a single project; having an overly theoretical context; and having too much freedom, which could lead to confusion.